Empowerment of women from pre-prosperous families through business mentoring - Zakiyah, Zakiyah; Erziaty, Rozzana; Wahab, Abdul (Universitas Muhammadiyah Magelang, 2025)
Women's micro-enterprises, organized within the Sungai Ulin Joint Business Group, have fostered family economic activities through the production of rempeyek (a traditional Indonesian cracker). The challenges they face lie in the areas of production and management. Innovation in rempeyek production by creating new flavor variations is needed to expand consumer choice. The community service method employed was Participatory Rural Appraisal (PRA) through counseling and business mentoring. The results of the activities showed an increase in understanding (cognitive) from an average of 2.33 to 5.31.